PLC FUNCTION BLOCK CREATION FOR MINIMIZING DATA LINK LIMITATION ON CC-LINK-BASED CONVEYOR HANDLING SYSTEM - Pongswatd, Sawai; Niyomtamarat, Patipak; Kummool, Sart; Thepmanee, Teerawat (My University, 2022)
In order to solve a facing network capacity problem when improving an existing conveyor handling system controlled by programmable logic controllers (PLCs) on master-slave control and communication link (CC-Link) network at a wooden pallet manufacturer, this article presents a software technique for short-term solution. For new requirements to upgrade a pallet sortation to be automated by installing new robotic handling unit, a slave PLC using an interface module modeled FX2N-32CCL (or slave PLC1) cannot receive all specified data of pallet production models from an existing master PLC using intelligent module modeled QJ61BT11N in one communication cycle due to limited data links. To overcome this limitation, a PLC function block creation based on data sorting approach is proposed. Two new function blocks named FB SEND and FB RECEIVE are created based on IEC61131-3 standard for adding to the existing ladder diagrams, which execute on the master PLC central processing unit (CPU) and slave PLC1 CPU, respectively. Experimental results verify that the created function blocks can provide data transfers correctly between the specified sources and destinations. The data received at the slave PLC1 CPU are similar to the data sent from the master PLC CPU. With the proposed solution, the desired conveyor handling system can be upgraded according to user’s requirements.
Keywords: CC-Link; Data link; Function block; Master-slave configuration; Programmable logic controller